Pengaruh Penerapan Total Productive Maintenance Terhadap Kinerja Perusahaan Farmasi di Jawa Timur - Widiaswanti, Ernaning (Rekayasa, 2009)
Many companies  increase its organizational  capability  through investing  in such programs  as Just In Time (JIT) and Total Quality Management (TQM). Thebenefit of these programs, however, seems always limited because of less reliab1e equipment. Many companies find Total Productive Maintenance (TPM) to add into the existed programs in order to have continued improvement. Pharmaceutical industry becomes one that uses TPM to maintain its reliabilityfrom the equipment used to suP.E...ort production process. The objective of research aims at examining and analyzing the effect of "1otal Productive Maintenance (TPM) application, comprising tohousekeeping, cross training, teams, q1erator involvement, disciplined planning, information tracking, and schedule compliance, on the performance of pharmaceutical companies in East Java. The number of sample consisting of19 pharmaceutical companies. Data analysis considers multiple linear regresszon analysis.Keyword : Total Productive Maintenance, Company Performance, Pharmaceutical Company, Multiple Linear Regression Analysis